Searching for arrowheads: an inquiry into approaches to indigenous research using a tribal methodology with a Nêhiýaw Kiskêýihtamowin worldview - Kovach, Margaret (2006)
Through a qualitative, interdisciplinary inquiry of six Indigenous scholars who had completed or were currently enrolled in Education. Social Work or Family Studies doctoral programs, this study explores Indigenous methodologies with a specific focus on methodologies flowing from a Nehiyaw Kiskeyihtamowin (Plains Cree knowledges). The study asked six scholars. four being of Cree ancestry, if they believed that there was a distinctive Indigenous methodological approach to research and if so what did it entail. Secondly, the study inquired into how Indigenous knowledges informed their research decisions and the applications of those decisions. Finally, given that each of these individuals were, or had been, enrolled in western doctoral programs this inquiry asks what were the challenges of using Indigenous methodologies based on an Indigenous worldview. Findings from this study include an assertion of Indigenous methodologies and that this is a relational approach to research: that Indigenous methodologies flow from an Indigenous worldview while needing to be congruent with specific cultural ways and protocols of the differing nations; that Indigenous methodologies encompass an inclusive, broad range of knowing which demands a holistic interpretation of ethical considerations; and that Indigenous methodologies includes decolonizing theory and action. In terms of application, the six individuals of this study affirm that research decisions (e.g. research methods) need to be congruent with the respective cultural epistemologies. Through their research stories. they provide examples of how they achieved this congruency in their methodology. Further, the study illustrates significant factors, such as allies, in nurturing the advancement of this approach to research in western universities. To inquire into this topic, an Indigenous methodology flowing from a Nehiyaw epistemology was used. This approach honours a relational worldview involving both the stories of the research participants as well as a reflective ...